Evaluation of The Effectiveness of The Use of Financial Statements as A Basis for Assessing Financial Performance at CV Cita Mandiri, Batu City, East Java - Maria Yunita Seran; Elly Lestari; Yuni Setyawati (IRDH International Journal of Social Sciences & Humanities, 2025)
The purpose of this study is to evaluate the effectiveness of the use of financial statements as the basis for assessing financial performance in CV Cita Mandiri Batu City. The research conducted is a research using qualitative methods. The data used is in the form of financial statements for the 2024 period and interviews with 3 informants, namely business owners, owners' husbands, and production employees. The data analysis method is a way of description, by presenting the results of interviews, presenting financial statements and drawing conclusions. The results of the study prove that the use of financial statements is effective as a basis for assessing financial performance in CV Cita Mandi. The form of financial statements made by CV Cita Mandiri includes a list of expenses and income, balance sheets, income statements and notes on financial statements. Financial statements are one of the important sources of information for SME owners to make business decisions. The benefits of financial statements help SMEs provide relevant and reliable financial information. The factors that are obstacles in financial reporting on CV Cita Mandir are that there are no employees in the field of accounting, so that the business owner makes financial reports manually in the accounting book and copies them to the computer using the Microsoft Excel program. The impact of employees not being able to make financial reports is that the preparation of financial statements is made manually in the accounting books, so that overall the financial statements made are not accurate.